A meta-analysis of genome-wide association studies identifies novel variants associated with osteoarthritis of the hip. Issue 12 (29th August 2013) - Evangelou, Evangelos; Kerkhof, Hanneke J; Styrkarsdottir, Unnur; Ntzani, Evangelia E; Bos, Steffan D; Esko, Tonu; Evans, Daniel S; Metrustry, Sarah; Panoutsopoulou, Kalliope; Ramos, Yolande F M; Thorleifsson, Gudmar; Tsilidis, Konstantinos K; et al.
Abstract : Objectives: Osteoarthritis (OA) is the most common form of arthritis with a clear genetic component. To identify novel loci associated with hip OA we performed a meta-analysis of genome-wide association studies (GWAS) on European subjects. Methods: We performed a two-stage meta-analysis on more than 78 000 participants. In stage 1, we synthesised data from eight GWAS whereas data from 10 centres were used for 'in silico' or 'de novo' replication. Besides the main analysis, a stratified by sex analysis was performed to detect possible sex-specific signals. Meta-analysis was performed using inverse-variance fixed effects models. A random effects approach was also used. Results: We accumulated 11 277 cases of radiographic and symptomatic hip OA. We prioritised eight single nucleotide polymorphism (SNPs) for follow-up in the discovery stage (4349 OA cases); five from the combined analysis, two male specific and one female specific. One locus, at 20q13, represented by rs6094710 (minor allele frequency (MAF) 4%) near the NCOA3 (nuclear receptor coactivator 3) gene, reached genome-wide significance level with p=7.9×10 −9 and OR=1.28 (95% CI 1.18 to 1.39) in the combined analysis of discovery (p=5.6×10 −8 ) and follow-up studies (p=7.3×10 −4 ). We showed that this gene is expressed in articular cartilage and its expression was significantly reduced in OA-affected cartilage. Moreover, two loci remained suggestive associated; rs5009270 at 7q31 (MAF 30%, p=9.9×10 −7, OR=1.10) and rs3757837 at 7p13 (MAF 6%, p=2.2×10 −6, OR=1.27 in male specific analysis). Conclusions: Novel genetic loci for hip OA were found in this meta-analysis of GWAS.